2017
DOI: 10.1115/1.4035048
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Impeller Outflow Conditions on the Performance of Vaned Diffusers

Abstract: Highly-loaded impellers, typically used in turbocharger and gas turbine applications, exhaust an unsteady, transonic flow that is non-uniform across the span and pitch and swirling at angles approaching tangential. With the exception of the flow angle, conflicting data exist regarding whether these attributes have substantial influence on the performance of the downstream diffuser. This paper quantifies the relative importance of the flow angle, Mach number, non-uniformity and unsteadiness on diffuser performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Nowadays, numerical simulations have been extensively used to investigate the complex flow characteristics within the turbomachines, due to development of highperformance computers and advanced computational fluid dynamics algorithms [19][20][21][22][23]. Everitt et al [19] quantified the role of outflow from the impeller exit in the compressor performance with vaned diffusers. They found that the effectiveness is well correlated to the mixed-out average flow angle.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, numerical simulations have been extensively used to investigate the complex flow characteristics within the turbomachines, due to development of highperformance computers and advanced computational fluid dynamics algorithms [19][20][21][22][23]. Everitt et al [19] quantified the role of outflow from the impeller exit in the compressor performance with vaned diffusers. They found that the effectiveness is well correlated to the mixed-out average flow angle.…”
Section: Introductionmentioning
confidence: 99%